2010
DOI: 10.1111/j.1751-1097.2010.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage in Response to Natural Levels of UV‐B Radiation in Larvae of the Tropical Sea Urchin Tripneustes gratilla

Abstract: To assess the effects of UV radiation (280-400nm) on development, oxidative damage and antioxidant defence in larvae of the tropical sea urchin Tripneustes gratilla, a field experiment was conducted at two depths in Aitutaki, Cook Islands (18.85°S, 159.75°E) in May 2008. Compared with field controls (larvae shielded from UV-R but exposed to VIS-radiation), UV-B exposure resulted in developmental abnormality and increases in oxidative damage to proteins (but not lipids) in embryos of T. gratilla held at 1m dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…The transparent embryo enables easy observation of malformation, making it possible to detect sub-lethal effects of pollutants on multicellular body formation at an early stage in development. To date, the stressors that have been examined using the sea urchin as a model include physico-chemical changes in the water, such as acidic pH (Dupont et al, 2010), hypoxia (Kodama et al, 2010), UV Schröder et al, 2005;Bonaventura et al, 2005Bonaventura et al, , 2006Lister et al, 2010aLister et al, , 2010bRusso et al, 2010), X-rays Bonaventura et al, 2011), and chemicals such as antifouling agents/pesticides (Garaventa et al, 2010;Aluigi et al, 2010), endocrine disruptors (Sugni et al, 2010;Horiguchi et al, 2010) and metals (Pinsino et al, 2014;Kiyomoto et al, 2010). Natural toxins represent a major source of stress for marine organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The transparent embryo enables easy observation of malformation, making it possible to detect sub-lethal effects of pollutants on multicellular body formation at an early stage in development. To date, the stressors that have been examined using the sea urchin as a model include physico-chemical changes in the water, such as acidic pH (Dupont et al, 2010), hypoxia (Kodama et al, 2010), UV Schröder et al, 2005;Bonaventura et al, 2005Bonaventura et al, , 2006Lister et al, 2010aLister et al, , 2010bRusso et al, 2010), X-rays Bonaventura et al, 2011), and chemicals such as antifouling agents/pesticides (Garaventa et al, 2010;Aluigi et al, 2010), endocrine disruptors (Sugni et al, 2010;Horiguchi et al, 2010) and metals (Pinsino et al, 2014;Kiyomoto et al, 2010). Natural toxins represent a major source of stress for marine organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Embryos of this Antarctic species, as many animals adapted to low temperatures, show moderate to high levels of both SOD and CAT enzymes when compared with other marine larvae (Lister et al, 2010a). Similar field experiments on the tropical T. gratilla embryos exposed to UVB, at the depth of 1 and 4 m in the water column, showed that these embryos had increased enzymatic activities of SOD, glutathione peroxidase (GPx) and glutathione reductase (GR), when compared with embryos protected from UVB and used as controls (Lister et al, 2010b). The proteomic analyses on early S. purpuratus embryos showed that UVB induced changes in a large number of proteins that are biomarkers of oxidative stress, i.e.…”
Section: Hsp70 and Anti-oxidative Proteinsmentioning
confidence: 93%
“…Lipids oxidative damage occurred in T. gratilla embryos exposed to solar radiation at depths of 1 and 4 m in field experiments (Lister et al, 2010b). In parallel, the activities of antioxidant enzymes significantly increased (see Section 3.2.1), indicating that embryos upregulate their antioxidant defenses to provide protection to oxidative damages of proteins as well as lipids (Lister et al, 2010b).…”
Section: Pathways Activated By Uvrmentioning
confidence: 96%
See 2 more Smart Citations